UPAYA MENINGKATKAN PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM DENGAN MENERAPKAN MODEL PENGAJARAN KOLABORASI - Jalalaudin, Jalaludin (Universitas Tanjungpura, 2020)
This research is based on the problem (a) How is the improvement of PAI learning achievement by applying the collaborative teaching model for the fourth grade students of SDN 14 Pulau Kumbang in academic year 2017/2018 (b) What is the effect of the collaborative teaching model on the motivation of PAI learning for the fourth grade students of SDN 14 Pulau Kumbang 2017/2018. While the objectives of this research are (a) to find out the improvement of PAI learning achievement after the implementation of the collaborative teaching model (b) to know the effect of PAI learning motivation after applying the collaborative teaching model. This research uses action research as much as three cycles. Each round consists of four stages: planning, observing, reflecting and revising. The target of this research is the fourth grade students of SDN 14 Pulau Kumbang in academic year 2017/2018. The data obtained in the form of formative test results, observation sheets of teaching and learning activities. From the results of analysts, it was found that student achievement increased from cycle I to cycle III namely, cycle I (73.17%), cycle II (82.93%), cycleIII (95.12%). The conclusion of this study is the cooperative learning method can positively influence the achievement and motivation of students in class IV SDN 14 Pulau Kumbang in academic year 2017/2018 and this learning model can be used as an alternative to PAI learning.